2014
DOI: 10.1177/0960327114556787
|View full text |Cite
|
Sign up to set email alerts
|

Usage of whey protein may cause liver damage via inflammatory and apoptotic responses

Abstract: The purpose of this study was to investigate the long- and short-term inflammatory and apoptotic effects of whey protein on the livers of non-exercising rats. Thirty rats were divided into three groups namely (1) control group, (2) short-term whey (WS) protein diet (252 g/kg for 5 days), and (3) long-term whey (WL) protein diet (252 g/kg for 4 weeks). Interleukin 1β (IL-1β), IL-6, tumor necrosis factor α (TNF-α), and cytokeratin 18 (CK-18-M30) were assessed using enzyme-linked immunosorbent assay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…However, the young man was consuming also other supplements such as Nopal ® , an extract from cactus of Opuntia genus, used as source of dietary fibers in the management of overweight (Grube et al 2013), GNC Mega Men Sport ® , a complex mixture containing numerous vitamins, minerals among which are chromium, branched chain amino acids, l-carnitine, lycopene, choline, zeaxanthin, astaxanthin, alpha-lipoic acid and others and, finally, whey protein. The latter, even if reputed a hepatoprotective substance (Gad et al 2011), has been shown to cause liver damage in humans and in laboratory experiments (Vilella et al 2013;Gürgen et al 2014;Whitt et al 2008). Moreover, chromium has been suspected of hepatotoxicity as already stated.…”
Section: Discussionmentioning
confidence: 87%
“…However, the young man was consuming also other supplements such as Nopal ® , an extract from cactus of Opuntia genus, used as source of dietary fibers in the management of overweight (Grube et al 2013), GNC Mega Men Sport ® , a complex mixture containing numerous vitamins, minerals among which are chromium, branched chain amino acids, l-carnitine, lycopene, choline, zeaxanthin, astaxanthin, alpha-lipoic acid and others and, finally, whey protein. The latter, even if reputed a hepatoprotective substance (Gad et al 2011), has been shown to cause liver damage in humans and in laboratory experiments (Vilella et al 2013;Gürgen et al 2014;Whitt et al 2008). Moreover, chromium has been suspected of hepatotoxicity as already stated.…”
Section: Discussionmentioning
confidence: 87%
“…Initiating type (caspase -2, -8, -9, -10 and -12), is triggered autocatalysis upon sensing death signals; and killer type (caspase-3, -6, and -7) is triggered proteolysis by initiating caspases [89]. Gürgen et al [90] reported that when whey protein is used indiscriminately, and in the absence of sufficient physical activity, negative effects on the liver may occur, due to the increased apoptotic signs short-term, and increased inflammatory markers and hepatotoxicity long-term. They also reported increased levels of AST and ALT in whey protein-fed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, supplementation with approximately 7 g of whey protein daily for 2 months in Crohn`s patients was also well tolerated (Benjamin, Makharia et al 2012). Nevertheless, there have been some reports of liver toxicity in rats after treatment with 0.5 g /kg for 21 days (Żebrowska-Gamdzyk, Maciejczyk et al 2018), or following treatment with extremely high doses of whey proteins (252 g/kg for 4 weeks) (Gürgen, Yücel et al 2015).…”
Section: Safety and Tolerability Of Gsh Precursors And Nrf2 Activatorsmentioning
confidence: 99%